Let's examine the steps that Karim took to solve the quadratic equation \(x^2 + 5x - 24 = 0\) by grouping:
-
Step 1: \(x^2 + 8x + (-3x) - 24 = 0\)
- Here, Karim incorrectly chose \(8\) and \(-3\) to split the middle term \(5\). The correct factors that sum up to \(5\) and multiply to \(-24\) should be \(8\) and \(-3\), so this step seems acceptable at first glance.
-
Step 2: \((x^2 + 8x) + (-3x - 24) = 0\)
- This step correctly groups the terms.
-
Step 3: \(x(x + 8) + 3(x + 8) = 0\)
- Here, he factors out \(x\) from \(x^2 + 8x\) (correct) but he mistakenly factors out \(3\) from \(-3x - 24\) instead of \(-3\) as it should be factoring out \(-3\) from that term.
-
Step 4: \((x + 8)(x + 3) = 0\)
- This step results from a misapplication or misunderstanding of step 3.
-
Step 5: \(x + 8 = 0\) or \(x + 3 = 0\)
- This leads to the roots \(x = -8\) or \(x = -3\).
Karim's first error occurs in Step 3, where he incorrectly factored \(-3x - 24\). Instead, he should have factored out \(-3\), leading to correct factors.
Therefore, the correct answer is that Karim's first mistake occurs at Step 3.